Changes in tree size, not species diversity, underlie the low above‐ground biomass in natural forest edges. (27th March 2021) - Silva, Mateus Cardoso; Melo, Felipe Pimentel Lopes; van den Berg, Eduardo
Abstract: Questions: Forest's above‐ground biomass is an important component of the global carbon cycle and, in forest fragments, it tends to decrease near the edges. This edge effect on biomass can be due to the number and identity of species residing at edges or due to the context of edges constraining plant functioning regardless of the species. Here, we took advantage of species‐rich natural forest edges to test the role of species richness, composition, and context dependency in explaining why forest edges stock less above‐ground biomass than interiors. Location: Gallery forests in Brazilian savanna (latitude 21° S, longitude 44° W). Methods: We tested the relationship between species richness and above‐ground biomass in 49 forest plots (10, 142 trees). We used a novel adaptation of the Price equation to calculate the impact of species composition (losses and gains) and context dependency on the differences of above‐ground biomass between edges and interiors. Results: Differences in species richness and composition did not explain the lower above‐ground biomass of forest edges when compared to interiors. Biomass responses were context‐dependent, in which the same species achieved smaller sizes when it grew in the edge than in the interior. Conclusions: Our study shows that edge effects on biomass may operate independently of biodiversity as edges and interiors had a similar number of species but distinct above‐ground biomass. Indeed, in the studied natural forest patches, the edge context itself limits plant size and, thus, the above‐ground biomass stock. Beyond unveiling the underlying causes of edge effects on forest biomass, our results call for distinct policies to conserve both the carbon stocks in forest interiors but also the unique diversity of natural edges. Abstract : Changes in species number and identity did not explain lower above‐ground biomass in natural forest edges compared to interiors. We found that edges constrain tree stem diameter and height irrespective of its species. Policy‐making in Brazil's gallery forests must protect both carbon stored deep in the forest and the iconic diversity of natural and ancient forest edges.